An extension of Ben-Daya–Rahim (2000) and Rahim–Banerjee (1993) cost models for economic design of T2-control charts for multivariate deteriorating processes with preventive maintenance and early replacement. Issue 9 (3rd May 2018) - Pasha, M. A.; Moghadam, M. Bameni
ABSTRACT: Along with economic aspects of statistical quality control, monitoring multiple quality characteristics of industrial processes are usually crucial to mutual relation between customers and manufacturers. In addition, the possibility of age-dependent repair before failure and the preventive maintenance that reduce the shift rate to the out-of-control state of the process can also be applied to increase reliability of a system. To attain joint optimization of the maintenance level, the early replacement time, and the economic design parameters of control charts (the sample size, the sampling interval, and the control limits coefficient), the general approach of Ben-Daya and Rahim (2000 ) and Rahim and Banerjee (1993 ) is applied in this paper for multivariate process control. A numerical study assuming the Weibull shock model with increasing failure rate is performed due to its wide application in deteriorating processes.